Respuesta :
Answer:
x = 6i, -6i
Explanation:
x² = 1 - 37 (subtract)
x² = -36 (square root both sides)
x = ±√-36 (breakdown)
x = +√-36, -√-36 (simplify)
x = 6i, -6i
Answer:
- x = 6i, -6i
Step-by-step explanation:
[tex]\sf x^2=1-37[/tex]
Subtract 37 from 1 = -36
[tex]\boxed{\sf x^2=? :\: x=\sqrt{?},\:\:-\sqrt{?}}[/tex]
[tex]\sf x=\sqrt{-36}[/tex]
[tex]\sf x=-\sqrt{-36}[/tex]
Apply Radical Rule:-
[tex]\boxed{ \sf \sqrt{-a}=\sqrt{-1}\sqrt{a}}[/tex]
[tex]\sf \sqrt{-36}=\sqrt{-1}\sqrt{36}[/tex]
[tex]\sf \sqrt{-1}\sqrt{36}[/tex]
[tex]\boxed{\sf \sqrt{-1 }=i}[/tex]
[tex]\sf \sqrt{36}i[/tex]
[tex]\sf 6i[/tex]
___________
[tex]\sf x=-\sqrt{-36}[/tex]
[tex]\sf -\sqrt{-36}[/tex]
[tex]\sf -6i[/tex]
Therefore, x = 6i, -6i.